2007
DOI: 10.1186/1471-2105-8-413
|View full text |Cite
|
Sign up to set email alerts
|

Identifying dynamical modules from genetic regulatory systems: applications to the segment polarity network

Abstract: Background: It is widely accepted that genetic regulatory systems are 'modular', in that the whole system is made up of smaller 'subsystems' corresponding to specific biological functions. Most attempts to identify modules in genetic regulatory systems have relied on the topology of the underlying network. However, it is the temporal activity (dynamics) of genes and proteins that corresponds to biological functions, and hence it is dynamics that we focus on here for identifying subsystems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(65 citation statements)
references
References 14 publications
0
65
0
Order By: Relevance
“…Furthermore, our findings demonstrate the importance of considering functional aspects of biologically relevant network modularity [36][39].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Furthermore, our findings demonstrate the importance of considering functional aspects of biologically relevant network modularity [36][39].…”
Section: Discussionmentioning
confidence: 68%
“…However, it is recently being suggested that functional or dynamic rather than architectural network modularity may be most relevant for network functioning and evolution [36][40]. Note that architectural and functional modularity do not necessarily overlap.…”
Section: Introductionmentioning
confidence: 99%
“…This definition of a module in terms of dynamics and function is probably the most common. One way of disclosing modules in this sense as dynamic elements related to the attractors (point-like or periodic) of a (discrete time) network is given in [34].…”
Section: Modules and Actively Regulating Unitsmentioning
confidence: 99%
“…Such motifs thus provide a signature of the underlying phenotypic constraints. In some cases the motifs on their own lead to clear insights into the regulatory logic used, while in other cases it is necessary to consider the motifs in a larger context [196], for instance by taking into account interactions with adjacent motifs.…”
Section: Discussion Conclusion and Outlookmentioning
confidence: 99%